A Setting For Excellence : The Story of the Planning and Development of the Ann Arbor Campus of the University of Michigan - Mayer, Frederick W. (Book collections on Project MUSE., 2015)
"While there are times when the mix of old and new buildings and the chaotic activities of thousands of students can give a haphazard appearance to the university, campus planning has in fact become a highly refined form of architecture. This is demonstrated in a convincing fashion by this immensely informative and entertaining history of the evolution of the campuses of the University of Michigan by Fred Mayer, who served for more than three decades as the campus planner for the university during an important period of its growth during the late twentieth century. By tracing the development of the Michigan campus from its early days to the present, within the context of the evolution of higher education in America, Mayer provides a strong argument for the importance of rigorous and enlightened campus planning as a critical element of the learning environment of the university. His comprehensive history of campus planning, illustrated with photos, maps, and diagrams from Michigan's history, is an outstanding contribution to the university's history as it approaches its bicentennial in 2017. Perhaps more important, Mayer's book provides a valuable treatise on the evolution of campus planning as an architectural discipline"--